2002
DOI: 10.1046/j.1523-5378.2002.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Pronase on the Efficacy of Eradication Therapy Against Helicobacter pylori

Abstract: Pronase has an additive effect in curing H. pylori infection. Pronase has no apparent in vitro activity against H. pylori, but may improve the local delivery of antibiotics by virtue of its removal and disruption of the SMGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Pronase alone did not exhibit an inhibitory effect on H. pylori in vitro, even at concentrations of 3.3 ϫ 10 3 mg/liter, in previous studies (data not shown), which was consistent with previous reports demonstrating that pronase did not inhibit the growth of H. pylori (11). Misoprostol is a mucosal protective agent (26).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pronase alone did not exhibit an inhibitory effect on H. pylori in vitro, even at concentrations of 3.3 ϫ 10 3 mg/liter, in previous studies (data not shown), which was consistent with previous reports demonstrating that pronase did not inhibit the growth of H. pylori (11). Misoprostol is a mucosal protective agent (26).…”
Section: Discussionsupporting
confidence: 91%
“…A potentially useful method would be to directly improve the local drug concentration in the deep GML. According to Gotoh et al (11), quadruple therapy with lansoprazole, pronase, amoxicillin, and metronidazole could improve the efficacy of H. pylori eradication in humans, which may be due to the increased delivery of antibiotics at the site of infection by virtue of pronase's ability to remove and disrupt the GML. However, the doses of antibiotics were 500 mg of amoxicillin and 250 mg of metronidazole, and the times of therapy were three times daily for 2 weeks, which worsens compliance due to an additional drug being administered at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Taking these considerations into account, bioadhesive rifaximin formulations able to better and persistently cover gastric mucosa [70, 71], or combination with mucolytic agents, such as pronase or acetylcysteine [72, 73], need to be evaluated in order to better define the place of this antibiotic in our therapeutic armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…Pronase and N-acetyl cysteine have been used to change the mucus layer and potentially expose the bacteria. In one trial pronase given as 18,000 tyrosine units of pronase thrice daily for 2 weeks significantly increased the effectiveness of traditional triple therapy (eg, from 76.5 to 94%) 72 . Clearly, additional studies are needed.…”
Section: Thinking Outside the Box: The Use Of Treatment Enhancersmentioning
confidence: 99%